2013
DOI: 10.3766/jaaa.24.7.8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Objective and Subjective Benign Paroxysmal Positional Vertigo

Abstract: The results of the study indicated that individuals with both objective and subjective BPPV demonstrated significant improvement in DHI scores following CRM treatment. Additionally, there was no difference in DHI improvement for the subjective versus objective group suggesting CRM are effective for both subjective BPPV and objective BPPV. This improvement in DHI scores was also noted in the five-question DHI subscale with no significant difference noted between groups. These findings combined with previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
(30 reference statements)
2
15
3
Order By: Relevance
“…The decision not to use Frenzel goggles or videonystagmography in our study was deliberate as we wished to reproduce the conditions faced by GPs in routine practice. Response to the EM in terms of perceived disability was not in uenced by the presence or absence of nystagmus at baseline, supporting previous ndings by Huebner et al [39] and Marques et al [41]. Nonetheless, we cannot completely rule out the possibility that some of the patients in the S-BPPV group may have had vestibular neuritis or vestibular migraine.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The decision not to use Frenzel goggles or videonystagmography in our study was deliberate as we wished to reproduce the conditions faced by GPs in routine practice. Response to the EM in terms of perceived disability was not in uenced by the presence or absence of nystagmus at baseline, supporting previous ndings by Huebner et al [39] and Marques et al [41]. Nonetheless, we cannot completely rule out the possibility that some of the patients in the S-BPPV group may have had vestibular neuritis or vestibular migraine.…”
Section: Discussionsupporting
confidence: 83%
“…The higher proportion of patients with S-BPPV detected in our series compared with earlier series [14] [39] indicates that we may have underestimated the prevalence of O-BPPV. Patients seen in primary care often have early-stage nystagmus, which is more di cult to diagnosis, particularly if special tools such as Frenzel goggles or videonystagmography are not used [40].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Subjective BPPV, defined as a positive history of BPPV with a positional testing positive for vertigo but negative for nystagmus, has been studied [19][20][21]. Balatsouras et al [20] diagnosed and treated 45 patients with subjective BPPV.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the absence of vertigo may be the best indicator of success for CRP, and many trials also report the conversion from positive to negative DHT after EM as a secondary outcome, similar to reported rates of symptom resolution . Thus, the resolution of vertigo or nystagmus on the DHT may be evaluated separately due to the possible presence of subclinical BPPV . Our study showed that 117 (88.6%) of 132 patients with idiopathic PC‐BPPV had resolution of vertigo, and 108 (81.8%) patients had resolution of both vertigo and nystagmus on the DHT at the 1‐week follow‐up after CCRP.…”
Section: Discussionmentioning
confidence: 65%